2021
DOI: 10.1177/00219347211055331
|View full text |Cite
|
Sign up to set email alerts
|

Framing the Problematics of Choice and Legacy: A Reading of August Wilson’s The Piano Lesson as a Dilemma Tale

Abstract: The choice for a particular narrative architecture has been a major concern for the literary writer and to the African American literary writer, the use of African oral literary elements has been a resourceful option. The present study hypothesizes that August Wilson uses the dilemma tale as a narrative architecture in his The Piano Lesson play and argues that this narrative style helps Wilson to frame the dialogic surrounding what legacy is to the African American. The study reveals that tradition is problema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Alvarado [7] found that the ancestor became the ultimate decision makers with regards to the fate of the family heirloom. Bentum [8] discovered the way Wilson draws the reader into the creative meaning making process and make their own judgment. Mashaiekhy, M., & Pishkar, K. [9] discussed the absurdity of the female characters' position in Wilson' The Piano Lesson and The Fences.…”
Section: Introductionmentioning
confidence: 99%
“…Alvarado [7] found that the ancestor became the ultimate decision makers with regards to the fate of the family heirloom. Bentum [8] discovered the way Wilson draws the reader into the creative meaning making process and make their own judgment. Mashaiekhy, M., & Pishkar, K. [9] discussed the absurdity of the female characters' position in Wilson' The Piano Lesson and The Fences.…”
Section: Introductionmentioning
confidence: 99%